Non-Hodgkin’s Lymphoma Presenting as Isolated Peritoneal Lymphomatosis: A Case Report and Literature Review - Zhu, Min; Wu, Zhixuan; Yang, Zhaoxia; Ning, Bo; Yu, Shengjie; Gu, Xiling; Yu, Huihong (Frontiers in Oncology, 2021)
Peritoneal lymphomatosis is extremely rare and associated with poor prognosis. Most practitioners only pay more attention to peritoneal carcinomatosis. However, peritoneal lymphomatosis can be neglected and misdiagnosed. We report a teenager with 10 days of abdominal distension and pain accompanied by computed tomography scan suggesting diffuse thickening of peritoneum and omentum and abdominopelvic effusion. Tuberculous peritonitis and peritoneal carcinomatosis were initially suspected. However, it was finally confirmed as non-Hodgkin’s B-cell lymphoma by omentum biopsies. He achieved complete remission after chemotherapy and autologous stem cell transplantation. But unfortunately, he suffered a relapse and died ten months after diagnosis. Following a review of the literature, it can be concluded that the discovery of lymphomatosis in peritoneum is a rare finding. Lymphoma should be considered in the differential diagnosis of unexplained peritoneal thickening on computed tomography, and this case emphasizes the importance of early pathological diagnosis to make sure that the right treatment can be started opportunely.